Temporal Progression of Aortic Valve Pathogenesis in a Mouse Model of Osteogenesis Imperfecta - Kaitlyn Thatcher; Carol R. Mattern; Daniel Chaparro; Veronica Goveas; Michael R. McDermott; Jessica Fulton; Joshua D. Hutcheson; Brian R. Hoffmann; Joy Lincoln (Journal of Cardiovascular Development and Disease, 2023)
Organization of extracellular matrix (ECM) components, including collagens, proteoglycans, and elastin, is essential for maintaining the structure and function of heart valves throughout life. Mutations in ECM genes cause connective tissue disorders, including Osteogenesis Imperfecta (OI), and progressive debilitating heart valve dysfunction is common in these patients. Despite this, effective treatment options are limited to end-stage interventions. Mice with a homozygous frameshift mutation in col1a2 serve as a murine model of OI (oim/oim), and therefore, they were used in this study to examine the pathobiology of aortic valve (AoV) disease in this patient population at structural, functional, and molecular levels. Temporal echocardiography of oim/oim mice revealed AoV dysfunction by the late stages of disease in 12-month-old mice. However, structural and proteomic changes were apparent much earlier, at 3 months of age, and were associated with disturbances in ECM homeostasis primarily related to collagen and proteoglycan abnormalities and disorganization. Together, findings from this study provide insights into the underpinnings of late onset AoV dysfunction in connective tissue disease patients that can be used for the development of mechanistic-based therapies administered early to halt progression, thereby avoiding late-stage surgical intervention.